Article THE CHARACTERISTICS OF IMPLEMENTING DRAMA ACTIVITIES TO DEVELOP PUPILS’ COMMUNICATIVE COMPETENCE AT ACADEMIC LYCEUM: THE CHARACTERISTICS OF IMPLEMENTING DRAMA ACTIVITIES TO DEVELOP PUPILS’ COMMUNICATIVE COMPETENCE AT ACADEMIC LYCEUMTHE CHARACTERISTICS OF IMPLEMENTING DRAMA ACTIVITIES TO DEVELOP PUPILS’ COMMUNICATIVE COMPETENCE AT ACADEMIC LYCEUM - Axmadaliyeva, Xosiyatposhsho (Журнал иностранных языков и лингвистики, 2021)
THE CHARACTERISTICS OF IMPLEMENTING DRAMA ACTIVITIES TO DEVELOP PUPILS’ COMMUNICATIVE COMPETENCE AT ACADEMIC LYCEUM